2014
DOI: 10.1007/s10484-014-9262-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Single Session of Upper Alpha Neurofeedback for Cognitive Enhancement: A Sham-Controlled Study

Abstract: The minimization of the non-specific factors of neurofeedback (NF) is an important aspect to further advance in the understanding of the effects of these types of procedures. This paper investigates the NF effects of a single session (25 min) of individual upper alpha enhancement following a sham-controlled experimental design (19 healthy participants). We measured immediate effects after the training and 1-day lasting EEG effects (eyes closed resting state and task-related activity), as well as the event-lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 29 publications
8
42
0
Order By: Relevance
“…So, future research is warranted to further elaborate in a systematic manner on the potential impact of potential confounding factors (e.g., small sample sizes such as in Rasey et al 1995, see below for more details on confounding factors). Besides that, as suggested earlier by Gruzelier (2014b, c), placebo is still rarely used as we encountered it in only six studies (i.e., Bazanova et al 2013;Escolano et al 2014;Guez et al 2015;Hsueh et al 2016;Kober et al 2015;Wang and Hsieh 2013) to demonstrate the statistical superiority of the effect on the NFB training. However, according to the guidelines for the evaluation of clinical efficacy of psychophysiological interventions, the inclusion of control and placebo or sham feedback groups would enhance the validity within the current research field on NFB training (La Vaque et al 2002).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…So, future research is warranted to further elaborate in a systematic manner on the potential impact of potential confounding factors (e.g., small sample sizes such as in Rasey et al 1995, see below for more details on confounding factors). Besides that, as suggested earlier by Gruzelier (2014b, c), placebo is still rarely used as we encountered it in only six studies (i.e., Bazanova et al 2013;Escolano et al 2014;Guez et al 2015;Hsueh et al 2016;Kober et al 2015;Wang and Hsieh 2013) to demonstrate the statistical superiority of the effect on the NFB training. However, according to the guidelines for the evaluation of clinical efficacy of psychophysiological interventions, the inclusion of control and placebo or sham feedback groups would enhance the validity within the current research field on NFB training (La Vaque et al 2002).…”
Section: Discussionmentioning
confidence: 80%
“…However, this effect could not be sustained 1 day later. With regard to cognitive performance, Escolano et al (2014) found a significant improvement in the upper alpha training group as well as the sham group. Nevertheless, the improvement was larger in the augment group than the sham group.…”
Section: Upper Alpha Neurofeedback Trainingmentioning
confidence: 87%
See 1 more Smart Citation
“…One of these important factors is long-term memory. Recent studies have shown that neurofeedback training method is an effective intervention in improving decreased levels of student's memory struggled with dictation disorder [6,9,[27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…One of these important factors is long-term memory. Recent studies have shown that neurofeedback training method is an effective intervention in improving decreased levels of student's memory struggled with dictation disorder [6,9,[27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%